Interdisciplinary approach for bilateral maxillary canine: First premolar transposition with complex problems in an adult patient - Dhivakar Selvaraj; Jhonson Raja; Somasundaram Prasath (Wolters Kluwer Medknow Publications, 2013)
Adult patients seeking orthodontic care were increased nowadays not only on esthetic need but also on functional demand. But problems with adult patients were not only malocclusions but also dental caries, pulpal pathology, missing teeth, muco-gingival problems and loss of supporting structures. We report here a case of 35-year-old female with complete transposition referred as a positional interchange of two permanent teeth within the same quadrant of the dental arch along with gingival recession of the lower anteriors and missing molars. Gingival health was improved by free gingival graft in lower anteriors followed by fixed orthodontic procedure to correct transposition. Based on transposition crown recontouring and restoration was done along with replacement of missing molars with fixed prosthesis. Thus, proper treatment planning with interdisciplinary management improves not only the esthetics and occlusal relationship but also with stable results.